Self and peer correction to improve writing skill among students of third year “a” of bachillerato, afternoon session at 27 de Febrero high school in loja city during 2019-2020 school year - Jimenez Toledo, Amada Lizbeth (2020)
The purpose of this research work was to improve writing skill through self and peer correction strategies among students of third year “A” of bachillerato. The methods that were considered to develop this research were: scientific, descriptive, analytical/synthetic and statistical, which were used to obtain information about writing and the strategies already mentioned, also to describe, analyze, represent and interpret the data obtained. Likewise, tests and questionnaires were applied to thirty-three students at the beginning and at the end of the intervention plan. These instruments were useful to diagnose the knowledge that students had in writing, and their attitude towards the application of self and peer correction. The results demonstrated that participants had a significant improvement in the three aspects of writing as spelling, vocabulary, and mechanics. Self and peer correction involved students in the correction process, and allowed them to know what were their writing mistakes, and how to avoid them.